Stability properties of periodic traveling waves for the intermediate long wave equation - Angulo, Jaime [UNESP]; Cardoso, Eleomar; Natali, Fabio (European Mathematical Soc, 2017)
In this paper we determine orbital and linear stability of a class of spatially periodic wavetrain solutions with the mean zero property related to the intermediate long wave equation. Our arguments follow recent developments for the study of the stability of periodic traveling waves.
Keywords: Stability; periodic waves; ILW equation; evolution models